Hypoalbuminemia and complication incidence in hemodialysed uremic patients - Galić, Gordan (Array, 2009)
Abstract: Discussions whether hypoalbuminemia is just a marker for the malnutrition-inflammation syndrome as well as for the increased morbidity and mortality of those patients or is it an etiological factor, are becoming more and more intense. In this research of the relation between hypoalbuminemia and the complications that threaten the vascular access with special reference to infection, and consequently to the life of the patients treated with chronic haemodialysis, we have chosen 120 patients with terminal renal insufficiency (ESRD) treated at the Clinical Hospital Mostar by chronic haemodialysis. The chosen patients for this study were observed throughout a time period of 18 months. Only the patients who, at the moment of starting the research did not exhibit either a local or a systemic infection, as well as no signs of any other complication that might have endangered the vascular access and consequently the life of the patient, were selected.